N-acetylcysteine: a novel approach to methaemoglobinaemia in normothermic liver machine perfusion - George Clarke; Jingwen Mao; Yiyu Fan; Angus Hann; Amita Gupta; Anisa Nutu; Erwin Buckel; Kayani Kayani; Nicholas Murphy; Mansoor N. Bangash; Anna L. Casey; Isla Wootton; et al. (Scientific Reports, 2023)
Abstract Extended duration of normothermic machine perfusion (NMP) provides opportunities to resuscitate suboptimal donor livers. This intervention requires adequate oxygen delivery typically provided by a blood-based perfusion solution. Methaemoglobin (MetHb) results from the oxidation of iron within haemoglobin and represents a serious problem in perfusions lasting > 24 h. We explored the effects of anti-oxidant, N-acetylcysteine (NAC) on the accumulation of methaemoglobin. NMP was performed on nine human donor livers declined for transplantation: three were perfused without NAC (no-NAC group), and six organs perfused with an initial NAC bolus, followed by continuous infusion (NAC group), with hourly methaemoglobin perfusate measurements. In-vitro experiments examined the impact of NAC (3 mg) on red cells (30 ml) in the absence of liver tissue. The no-NAC group sustained perfusions for an average of 96 (range 87–102) h, universally developing methaemoglobinaemia (≥ 2%) observed after an average of 45 h, with subsequent steep rise. The NAC group was perfused for an average of 148 (range 90–184) h. Only 2 livers developed methaemoglobinaemia (peak MetHb of 6%), with an average onset of 116.5 h. Addition of NAC efficiently limits formation and accumulation of methaemoglobin during NMP, and allows the significant extension of perfusion duration.